Expansion of the Human Phenotype Ontology (HPO) knowledge base and resources. Issue Volume 47:Issue D1(2019) (22nd November 2018) - Köhler, Sebastian; Carmody, Leigh; Vasilevsky, Nicole; Jacobsen, Julius O B; Danis, Daniel; Gourdine, Jean-Philippe; Gargano, Michael; Harris, Nomi L; Matentzoglu, Nicolas; McMurry, Julie A; Osumi-Sutherland, David; Cipriani, Valentina; et al.
Abstract: The Human Phenotype Ontology (HPO)—a standardized vocabulary of phenotypic abnormalities associated with 7000+ diseases—is used by thousands of researchers, clinicians, informaticians and electronic health record systems around the world. Its detailed descriptions of clinical abnormalities and computable disease definitions have made HPO the de facto standard for deep phenotyping in the field of rare disease. The HPO's interoperability with other ontologies has enabled it to be used to improve diagnostic accuracy by incorporating model organism data. It also plays a key role in the popular Exomiser tool, which identifies potential disease-causing variants from whole-exome or whole-genome sequencing data. Since the HPO was first introduced in 2008, its users have become both more numerous and more diverse. To meet these emerging needs, the project has added new content, language translations, mappings and computational tooling, as well as integrations with external community data. The HPO continues to collaborate with clinical adopters to improve specific areas of the ontology and extend standardized disease descriptions. The newly redesigned HPO website (www.human-phenotype-ontology.org ) simplifies browsing terms and exploring clinical features, diseases, and human genes.